Black and Latinx workers reap lower rewards than White workers from years spent working in big cities - Maximilian Buchholz; Michael Storper (Proceedings of the National Academy of Sciences, 2025)
The large labor markets of big cities offer greater possibilities for workers to gain skills and experience through successively better employment opportunities. This “experience effect” contributes to the higher average wages that are found in big cities compared to the economy as a whole. Racial wage inequality is also higher in bigger cities than in the economy on average. We offer an explanation for this pattern, demonstrating that there is substantial racial inequality in the economic returns to work experience acquired in big cities. Using data from the National Longitudinal Survey of Youth, 1979 we find that each year of work experience in a big city increases Black and Latinx workers’ wages by about one quarter to half as much as White workers’ wages. A substantial amount of this inequality can be explained by further racial disparities in the benefits of high-skill work experience. This research identifies a heretofore unknown source of inequality that is distinctly urban in nature, and expands our knowledge of the challenges to reaching interracial wage equality.